ANTI-CRISIS SOLUTIONS FOR THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED BUSINESSES AS A FACTOR IN IMPROVING THE ECONOMIC SECURITY OF THE STATE - K. V. Glukhov; I. A. Solovev (Вестник университета)
The article presents anti-crisis measures to support small and medium-sized businesses implemented by the  Government of the Russian Federation in the COVID-19 pandemic. The paper reviewed also the foreign experience  of using measures to support small and medium-sized businesses in the context of the spread of a new coronavirus infection and proposed measures to improve the effectiveness of anti-crisis programs to support small and medium-sized businesses during the spread of coronavirus infection. The authors used in this article the following research methods: analysis and generalization of Russian and foreign anti-crisis measures. The study proposed, based on this analysis, measures to improve the effectiveness of anti-crisis programs to support small  and medium-sized businesses during the spread of coronavirus infection in the Russian Federation.